Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Laptop Lenovo Pada Mahasiswa Sekolah Tinggi Ilmu Ekonomi Pancasetia Banjarmasin - Jayen, Fredy; Kadir, Abdul; Amrulloh, Rifqi; Hadi, Abdul (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
This study aims to examine the effect of product quality and price on purchasing decisions of Lenovo laptops for students of the Sekolah Tinggi Ilmu Ekonomi Pancasetia Banjarmasin. This researcher needs because to know the effect of which variable dominates. The type of research used is correlational research. This research is quantitative in nature. The population and sample in this study were 38 students at STIE Pancasetia Banjarmasin, data were collected through questionnaires distributed to respondents. The independent variables in this study are product quality (X1) and price (X2), while the dependent variable is the purchase decision (Y). Data were analyzed using Instrument Test, Classical Assumption Test, and Multiple Linear Regression. The results of this study indicate that product quality and price partially and simultaneously have a positive and significant effect on the decision to purchase a Lenovo laptop for students at the Sekolah Tinggi Ilmu Ekonomi Pancasetia Banjarmasin, and the more dominant variable in this study is product quality.